Mozambican immigrants to South Africa: Their xenophobia and discrimination experiences. Issue 3 (4th May 2018) - Moagi, Miriam; Wyatt, Gail; Mokgobi, Maboe; Loeb, Tamra; Zhang, Muyu; Davhana-Maselesele, Mashudu
Abstract : We explored Mozambican immigrants' lived experiences of xenophobia and discrimination in South Africa. Informants were 15 Mozambican immigrants (female = 7, male = 8) living in an informal settlement in Zandspruit, Gauteng Province. They completed open-ended written narratives on xenophobic and discriminatory experiences. Following thematic analysis, we identified three themes to characterise the Mozambican immigrants' experiences of xenophobia and discrimination: (i) abusive attitudes, (ii) ethnic discrimination, and (iii) scapegoating. The Mozambican immigrants' experiences of xenophobia and discrimination are consistent with findings from the extant international literature on ingroup/outgroup social strife with real or perceived scarcity of resources.